The Romans as Viewed by Arabic Authors in the 9th and 10th Centuries A.D. - Giannakis, Elias (Richtmann Publishing, 2012)
The question whether Muslims of non-Arab origin were culturally superior to the Arab Muslims was hotly debatedwithin the society of the Baghdad Caliphate from the middle of the eighth century A.D. onwards. Various groups that aimed atremoulding the political and social institutions and the direction of the Islamic culture brought in the subject of the characteristicsof the pre-Islamic and the contemporary civilized nations, their virtues and vices as well as their cultural history. It is in thiscontext that Arabic authors present their views about the Romans, their origin, their characteristics, their political and culturalhistory and their connection with other neighbouring nations. Such views are reflected in the works of three distinguishedMuslims authors who lived and wrote in Arabic during the period of the 9th and early 10th century A.D. This study aims atpresenting the views of the chosen three Arabic authors and the arguments they advanced as regards the history and culture ofRomans.